Sevoflurane augmentation in treatment-resistant depression: a clinical case study. (October 2020) - Wang, Shikai; Cheng, Shanfei; Feng, Min; Guo, Ping; Qian, Mincai; Shen, Xinhua; Chen, Runsen; Wang, Gang
Compared with other inhaled anaesthetics, sevoflurane has a faster onset and offset, causes less irritation to the mucous membranes, and has a better safety profile. These characteristics warrant investigating the effect of sevoflurane in depression. In this Case Report, we describe that sevoflurane treatment was feasible and well tolerated by a patient with treatment-resistant depression (TRD). Sevoflurane had rapid and durable antidepressant effects, with few adverse effects. Moreover, the patient showed significant improvements in neurocognitive measurements. Our preliminary results suggest that further clinical trials are needed to determine the independent efficacy and safety of sevoflurane in patients with TRD.